Efeitos do curcumin na modulação da inflamação e reabsorção óssea em dois modelos de doença periodontal em roedor - Guimarães, Morgana Rodrigues [UNESP] (2010)
Curcumin, a polyphenol derived from turmerics (Curcuma longa), has been shown to down regulate the activity of transcription factors NF-ĸB and AP-1 and to inhibit the expression the several inflammatory mediators. Its therapeutic applications have been studied in a variety of conditions, including as colitis, rheumatoid arthritis, cancer, psoriasis; but this is the first study to assess the effects of curcumin on periodontal disease in vivo. Periodontal disease initiation and progression occurs as a consequence of the host response to microorganisms of the dental biofilm. An improper immune response leads to overproduction of inflammatory cytokines and consequently periodontal attachment loss and bone resorption. In vitro study, we stimulated Raw 264.7 murine macrophages with E.coli LPS in the presence and absence of noncytotoxic concentrations of curcumin and of the biochemical inhibitors of NF-kB and p38 MAPK. RT-qPCR and ELISA were used to determine the expression of IL-6, TNFalpha and Cox-2/PGE2 at mRNA and protein levels. Western-blot was used to assess the effect of curcumin on LPS-induced activation of MAPKinases and NF-kB. In the vivo study, experimental periodontal disease was induced in rats by placing cotton ligatures around both lower first molars and injecting LPS in the gingival tissues on the palatal aspect of upper first molars (30 ug LPS, 3 times/week for 2 weeks). Curcumin was given to the rats by daily oral gavage in two doses (30 and 100 mg/Kg) during the 2 week-duration of the experiment. Control animals received ligatures and injection of LPS but only the corn oil vehicle by gavage and negative control animals were untouched. RT-qPCR and ELISA were used to determine the expression of IL-6, TNFalpha and PGE-2 synthase on the gingival tissues. The inflammatory status was evaluated by stereometric analysis, whereas modulation of p38 MAPK and NK-kB signaling was assessed by western...